2018
DOI: 10.21037/qims.2018.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Spleen and splenic vascular involvement in acute pancreatitis: an MRI study

Abstract: Splenic vascular involvement and splenomegaly were common in AP. The vascular involvement was associated with the severity of AP. This complication should be considered when severity and prognosis of AP are assessed. Quantitative analysis of the spleen with IVIM might be a useful imaging biomarker for splenic perfusion changes in AP, especially in those with splenomegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…We also observed that patients with splenic vein thrombosis determined in the late phase of AP showed signs of splenic vein phlebitis on their initial MRI scan. This new finding was probably due to early-phase vein inflammation, which eventually damages the endothelium, rendering the vessel susceptible to late-phase thrombosis (20,27). Also, patients with splenic vein thrombosis detected by initial MRI exhibited thrombus absorption on repeat MRI after treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We also observed that patients with splenic vein thrombosis determined in the late phase of AP showed signs of splenic vein phlebitis on their initial MRI scan. This new finding was probably due to early-phase vein inflammation, which eventually damages the endothelium, rendering the vessel susceptible to late-phase thrombosis (20,27). Also, patients with splenic vein thrombosis detected by initial MRI exhibited thrombus absorption on repeat MRI after treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, 44% of patients with splenic vein phlebitis had splenic vein stenosis in the early phase of AP. These new MRI findings may be explained by the close anatomic relationship between peripancreatic vasculatures and the pancreas itself, which results in local inflammatory spread and a weakened venous wall that is prone to collapse (17)(18)(19)(20). Interestingly, following treatment, the MRI signs of portosplenomesenteric vein phlebitis disappeared in most of these patients, suggesting that portosystemic vein phlebitis might be considered as a complementary sign for treatment evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…In acute pancreatitis, the spleen is also a commonly involved organ; common splenic abnormalities are splenomegaly and splenic infarction. In addition to routine sequences, quantitative analysis of the spleen with IVIM sequences might be useful for visualizing splenic perfusion changes in AP (14).…”
Section: Gastrointestinal Tract Involvementmentioning
confidence: 99%
“…Studies have shown that MRI can display positive correlations between the time of improvement of the gastrointestinal tract abnormalities and the time of hospitalization, the disappearance time of abdominal pain and abdominal distention, and the normal time of amylase recovery and the recovery time of the diet (47). MRI can also show peripancreatic vascular changes, and the severity of vascular involvement is positively correlated with the severity of AP (14). In addition, the incidence of liver and kidney dysfunction, pulmonary inflammation, perirenal space involvement, interfascial plane involvement and abdominal wall edema increases with the severity of AP (50)(51)(52).…”
Section: Mri For the Severity Of Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation